Pelaksanaan Tugas dan Kewenangan Jaksa di Bidang Perdata dan Tata Usaha Negara - Muhammad Insa Ansari; Indra Kesuma Hadi (Universitas Syiah Kuala, 2013)
ABSTRACT: In civil and administrative procedure fields, executor by its special authority can have power to act inside or outside court on behalf of the state or government. However, practically, there is not all claim of civil case and administrative is referring to the state, government, provincial government and working unit of local government, local government of district and municipality and this working unit are asking the executor to represent them. In fact, in the level of General Executor, High Executor and Magistrate Executor have the unit working on civil case and administrative case based on its duties and authorities. Duties and Authorities of Executor in Terms of Civil and Administrative Procedure